Defining the essential anatomical coverage provided by military body armour against high energy projectiles. Issue 4 (13th August 2015) - Breeze, John; Lewis, E A; Fryer, R; Hepper, A E; Mahoney, Peter F; Clasper, Jon C
Abstract : Introduction: Body armour is a type of equipment worn by military personnel that aims to prevent or reduce the damage caused by ballistic projectiles to structures within the thorax and abdomen. Such injuries remain the leading cause of potentially survivable deaths on the modern battlefield. Recent developments in computer modelling in conjunction with a programme to procure the next generation of UK military body armour has provided the impetus to re-evaluate the optimal anatomical coverage provided by military body armour against high energy projectiles. Methods: A systematic review of the literature was undertaken to identify those anatomical structures within the thorax and abdomen that if damaged were highly likely to result in death or significant long-term morbidity. These structures were superimposed upon two designs of ceramic plate used within representative body armour systems using a computerised representation of human anatomy. Results and conclusions: Those structures requiring essential medical coverage by a plate were demonstrated to be the heart, great vessels, liver and spleen. For the 50th centile male anthropometric model used in this study, the front and rear plates from the Enhanced Combat Body Armour system only provide limited coverage, but do fulfil their original requirement. The plates from the current Mark 4a OSPREY system cover all of the structures identified in this study as requiring coverage except for the abdominal sections of the aorta and inferior vena cava. Further work on sizing of plates is recommended due to its potential to optimise essential medical coverage.